USAHATANI PEPAYA CALIFORNIA: ANALISIS KELAYAKAN FINANASIAL SUATU STUDI KASUS DI DESA BENDANG RAYA KECAMATAN TENGGARONG KABUPATEN KUTAI KERTANEGARA - Ida Bagus Made Agung Dwijatenaya; Agung Enggal Nugroho; Ahmad Iskandar (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
The aims of this experiment was to determine the effect of the application of Agrib Compost liquid organic fertilizer to the growth of bud grafting seedling of Lai (Durio kutejensis HASSK. BECC) var. Mahakam. The experiment used a Randominzed Block Design (RCBD) with Agrib Compost liquid organic fertilizer treatment (P) 8 level and  3 tests made up of  p0 = without treatment (control), p1 = (2 ml L-1 water), p2 = (4 ml L-1 water), p3 = (6 ml L-1 water), p4 = (8 ml L-1 water), p5 = (10 ml L-1 water), p6 = (12 ml L-1 water), p7 = (14 ml L-1 water). The result of the experiment indicated that the treatment of Agrib Compost liquid organic fertilizer, it had a very significant effect to the age of broken buds but had no significant effect to the length of bud  parameters, the number of leaves  and the diameter of the stem. The treatment of Agrib Compost liquid organic fertilizer 14 ml L-1 water, providing better growth in  age parameters  of broken buds, bud length, and the number of leaves.